Unexplored Molecular Features of the Entamoeba histolytica RNA Lariat Debranching Enzyme Dbr1 Expression Profile - Valdés, Jesús; Ortuño-Pineda, Carlos; Saucedo-Cárdenas, Odila; Mendoza-Figueroa, María S. (Frontiers in Cellular and Infection Microbiology, 2018)
The RNA lariat debranching enzyme (Dbr1) has different functions in RNA metabolism, such as hydrolyzing the 2’-5’ linkage in intron lariats, positively influencing Ty1 and HIV-1 retrotransposition, and modulating snRNP recycling during splicing reactions. It seems that Dbr1 is one of the major players in RNA turnover. It is remarkable that of all the studies carried out to date with Dbr1, to our knowledge, none of them have evaluated the expression profile of the endogenous Dbr1 gene. In this work, we describe, for the first time, that Entamoeba histolytica EhDbr1 mRNA has a very short half-life (less than 30 min) and encodes a very stable protein that is present until trophozoite cultures die. We also show that the EhDbr1 protein is present in the nuclear periphery on the cytoplasmic basal side, contrary to the localization of human Dbr1. Comparing these results with previous hypotheses and with results from different organisms suggests that Dbr1 gene expression is finely tuned and conserved across eukaryotes. Experiments describing the aspects of Dbr1 gene expression and Dbr1 mRNA turnover as well as other functions of the protein need to be performed. Particularly, a special emphasis is needed on the protozoan parasite E. histolytica, the causative agent of amoebiasis, since even though it is a unicellular organism, it is an intron-rich eukaryote whose intron lariats seem to be open to avoid intron lariat accumulation and to process them in non-coding RNAs that might be involved in its virulence.